2017
DOI: 10.1055/s-0043-113571
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunctions Predict Self-Restricted Driving Habits in Elderly People with or without Alzheimer’s Dementia

Abstract: The purpose of this study was to elucidate the impact of specific cognitive functions on self-restricted driving habits in healthy elderly drivers and patients suffering from mild cognitive impairment (MCI) and Alzheimer's dementia (AD). Our study population included 35 cognitively healthy controls, 10 MCI patients, and 16 patients with AD. All participants completed a neuropsychological examination and a self-reported questionnaire assessing driving habits and patterns. In challenging driving conditions, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
2
6
0
3
Order By: Relevance
“…In addition, it is to be noted that in our sample, no parameter of driving performance was found to be significantly correlated with memory detected by LM. This is compatible with the results of a previous study [48], which found that memory itself did not significantly contribute to the prediction of driving behaviors. Likewise, after adjusting for age, we found that there was no significant difference between the delayed recall of current drivers and retired drivers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it is to be noted that in our sample, no parameter of driving performance was found to be significantly correlated with memory detected by LM. This is compatible with the results of a previous study [48], which found that memory itself did not significantly contribute to the prediction of driving behaviors. Likewise, after adjusting for age, we found that there was no significant difference between the delayed recall of current drivers and retired drivers.…”
Section: Discussionsupporting
confidence: 93%
“…Further, a proportion of current drivers had voluntarily restricted their driving behaviors, such as driving only in familiar residential areas and for short distances, driving during the hours of low traffic, etc. The phenomenon of self-imposed restriction on driving behavior was also reported by Kurzthaler et al [48], who interpreted it as a compensatory strategy. In our sample, younger people, males, and those with longer driving experience were more likely to be current drivers, in the light of demographic and driving-related characteristics.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, and in accordance with prior research [ 8 ], we found an association between lower functional impairment and a higher likelihood of driving a car by oneself. Such result may be explained by the fact that driving a car reflects a process which is quite complex covering executive functions and reaction [ 24 ] as well as visual skills [ 25 ] (which are in turn associated with functional impairment [ 26 ]).…”
Section: Discussionmentioning
confidence: 99%
“…25 Particularly in complex traffic situations, drivers with ADD show more driving self-restriction due to impaired attention and executive functioning. 26 Search results show that ADD patients make significantly more driving errors than healthy older drivers. 27,28 In particular, they have difficulties in remembering routes or traffic rules 28,29 and in identifying landmarks or traffic signs.…”
Section: Alzheimer Disease Dementiamentioning
confidence: 98%